Differential adherence to combination antiretroviral therapy is associated with virological failure with resistance. - Gardner, Edward M; Sharma, Shweta; Peng, Grace; Huppler Hullsiek, Katherine; Burman, William J; MacArthur, Rodger D; Chesney, Margaret; Telzak, Edward E; Friedland, Gerald; Mannheimer, Sharon B (AIDS (London, England), 2008)
To investigate the occurrence of differential adherence to components of combination antiretroviral therapy and assess its predictors and association with virological failure and antiretroviral medication resistance.
Keywords: Antiretroviral Therapy, Highly Active; Drug Resistance, Viral; HIV Infections; HIV Protease Inhibitors; HIV-1; Humans; Patient Compliance; Prospective Studies; Reverse Transcriptase Inhibitors; Treatment Outcome; Viral Load